2016
DOI: 10.1515/msp-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability, electronic structure and magnetic properties of the new hypothetical half-metallic ferromagnetic full-Heusler alloy CoNiMnSi

Abstract: We investigated the structural stability as well as the mechanical, electronic and magnetic properties of the Full-Heusler alloy CoNiMnSi using the full-potential linearized augmented plane wave (FP-LAPW) method. Two generalized gradient approximations (GGA and GGA + U) were used to treat the exchange-correlation energy functional. The ground state properties of CoNiMnSi including the lattice parameter and bulk modulus were calculated. The elastic constants (C ij ) and their related elastic moduli as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Recently, Yaroub Al‐Douri et al have predicted the half‐metallic behaviors for many new full‐Heusler and proved the useful of these compounds in high performance technological applications [4–10]. Besides the full‐ and HH alloys, many others materials have also been found to be half‐metallic such as quaternary Heusler alloys [11–14] and double perovskite [15]. The particularity of these materials is the development of structural distortion at low temperature and under the pressure effect, in addition to their very high Curie temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yaroub Al‐Douri et al have predicted the half‐metallic behaviors for many new full‐Heusler and proved the useful of these compounds in high performance technological applications [4–10]. Besides the full‐ and HH alloys, many others materials have also been found to be half‐metallic such as quaternary Heusler alloys [11–14] and double perovskite [15]. The particularity of these materials is the development of structural distortion at low temperature and under the pressure effect, in addition to their very high Curie temperature.…”
Section: Introductionmentioning
confidence: 99%
“…By using the first-principle calculations, many recent studies regarding quaternary Heusler alloys have confirmed that these compounds exhibit HMF s behaviors with high spin polarizations and high Curie temperature T C , confirming their applications in spintronics devices [4][5][6][7][8][9][10][11][12][13].…”
mentioning
confidence: 79%
“…By using the first‐principle calculations, many recent studies regarding quaternary Heusler alloys have confirmed that these compounds exhibit HMF s behaviors with high spin polarizations and high Curie temperature T C , confirming their applications in spintronics devices [4‐13]. The study of the electronic structures of CoRhMnZ (ZAl, Ga, Ge, and Si) compounds revealed that CoRhMnGe and CoRhMnSi show a HMF and their total magnetic moments follows the Slater–Pauling rule, which indicates the half metallicity and high spin polarization for both compounds [6].…”
Section: Introductionmentioning
confidence: 87%
“…[55][56][57][58][59][60] Half-metallic QHAs have also been proposed for their promising electronic, magnetic, and thermoelectric properties due to their high power factors. [55][56][57][58][59][60][61][62][63] In the search for new thermoelectric materials, firstprinciples calculations can play a complementary role in both predicting new materials properties, as well as providing a theoretical basis for observed phenomena. [64] Benefits of firstprinciples exploratory research has been illustrated for some half-Heusler thermoelectrics.…”
Section: Introductionmentioning
confidence: 99%